Review of Graphene Growth From a Solid Carbon Source by Pulsed Laser Deposition (PLD) - Bleu, Yannick; Bourquard, Florent; Tite, Teddy; Loir, Anne-Sophie; Maddi, Chirandjeevi; Donnet, Christophe; Garrelie, Florence (Frontiers in Chemistry, 2018)
Graphene is a remarkable two-dimensional (2D) material that is of great interest to both academia and industry. It has outstanding electrical and thermal conductivity and good mechanical behavior with promising applications in electronic devices, supercapacitors, batteries, composite materials, flexible transparent displays, solar cells, and sensors. Several methods have been used to produce either pristine graphene or doped graphene. These include chemical vapor deposition (CVD), mechanical exfoliation, decomposition of SiC, liquid-phase exfoliation, pulsed laser deposition (PLD). Among these methods, PLD, which is routinely used for growing complex oxide thin films has proved to be an alternative to the more widely reported CVD method for producing graphene thin films, because of its advantages. Here we review the synthesis of graphene using PLD. We describe recent progress in preparing pristine graphene and doped graphene by PLD, including deposition processes and characterization. The goal of this complete survey is to describe the advantages of using the technique for graphene growth. The review will also help researchers to better understand graphene synthesis using the PLD technique.